Effect of physical exercise on workplace social capital: Cluster randomized controlled trial. Issue 8 (December 2015) - Andersen, Lars L.; Poulsen, Otto M.; Sundstrup, Emil; Brandt, Mikkel; Jay, Kenneth; Clausen, Thomas; Borg, Vilhelm; Persson, Roger; Jakobsen, Markus D.
Aims: While workplace health promotion with group-based physical exercise can improve workers' physical health, less is known about potential carry-over effects to psychosocial factors. This study investigates the effect of physical exercise on social capital at work. Methods: Altogether, 200 female healthcare workers (nurses and nurse's aides) from 18 departments at three hospitals were randomly allocated at the department level to 10 weeks of (1) group-based physical exercise at work during working hours or (2) physical exercise at home during leisure time. At baseline and follow-up, participants replied to a questionnaire concerning workplace social capital: (1) within teams (bonding); (2) between teams (bridging); (3) between teams and nearest leaders (linking A); (4) between teams and distant leaders (linking B). Results: At baseline, bonding, bridging, linking A and linking B social capital were 74 (SD 17), 61 (SD 19), 72 (SD 22) and 70 (SD 18), respectively, on a scale of 0–100 (where 100 is best). A group by time interaction was found for bonding social capital ( P =0.02), where physical exercise at work compared with physical exercise during leisure time increased 5.3 (95% confidence interval 2.3– 8.2)(effect size, Cohen's d = 0.31) from baseline to follow-up. For physical exercise at home during leisure time and exercise at work combined, a time effect ( P =0.001) was found for linking A social capital, with a decrease of 4.8 (95% confidence interval 1.9–7.6). Conclusions: Group-based physical exercise at work contributed to building social capital within teams at the workplace. However, the general decrease of social capital between teams and nearest leaders during the intervention period warrants further research.